2021
DOI: 10.1111/myc.13324
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐fungal agents in the treatment of chronic pulmonary aspergillosis: Systematic review and a network meta‐analysis

Abstract: Background Oral itraconazole and voriconazole are currently recommended in the initial management of chronic pulmonary aspergillosis (CPA). However, only a few studies have compared outcomes with different anti‐fungal agents (AFAs) in treating CPA. Herein, we perform a network meta‐analysis comparing the efficacy of different AFAs in CPA. Methods We searched the PubMed and EmBase databases to identify studies (either randomised‐controlled trials [RCTs] or observational) reporting treatment outcomes with AFAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Finally, no serological marker is available to assess the treatment response or relapse in CPA. 1,9,20 In cluster 2, treatment response could also be monitored by serially measuring serum total IgE, like ABPA. 18 Our study has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no serological marker is available to assess the treatment response or relapse in CPA. 1,9,20 In cluster 2, treatment response could also be monitored by serially measuring serum total IgE, like ABPA. 18 Our study has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence of hemoptysis is due to the presence of aspergilloma that keeps on eroding the vessels in wall of the cavity and formation of new collateral vessels. The drugs available against Aspergillosis include the polyene (amphotericin B), the azoles (itraconazole and voriconazole), and echinocandins [24]. Systemic use of antifungals has several limitations such as nephrotoxicity, unpredictable oral absorption, need for drug-level monitoring, a long duration of treatment, limited concentration in the aspergilloma cavity, and relapse after discontinuation [25].…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of this report is that we could follow the clinical courses in both cases for only less than two months and CPA usually requires treatment for at least six months [ 11 ]. One network-centric meta-analysis has recently reported that ITCZ is the best oral antifungal agent for the initial treatment of CPA [ 12 ]. Further studies on CPA treatment following COVID-19 are required.…”
Section: Discussionmentioning
confidence: 99%